Orthodontic Replacement of Lost Permanent Molar with Neighbor Molar: A Six-Year Follow-Up - Taisa Boamorte Raveli; Ricardo Lima Shintcovsk; Luegya Amorim Henriques Knop; Luana Paz Sampaio; Dirceu Barnabé Raveli (Case Reports in Dentistry)
Extraction is very frequent indication in orthodontic planning, especially when there are crowding, biprotrusion, and aesthetically unpleasant profiles. Next to extraction comes space closure, which represents a challenge for orthodontists because of extended treatment time, discomfort created for the patient, tissue tolerance, and stability concerns. When it comes to what mechanics to choose for space closure, loops present two major advantages in relation to sliding mechanics: absence of abrasion and possibility to reach pure dental translation. A case is presented where an adult female patient with early loss of the first lower permanent molars, minor lower crowding, and tooth biprotrusion was treated with upper first bicuspids extraction along with upper and lower space closure done with T-loops to promote best space closure control in order to correct the malocclusion and enhance facial aesthetics.